Analysis of Learning Obstacles in the Topic of Geometric Transformations - Aminah, Neneng; Rahadi, Ikman Nurhakim; Noto, Muhammad Subali; Rosita, Cita Dwi (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this research is to identify the learning obstacles experienced by students at Nurul Huda Jannatun Vocational High School. This study is a qualitative research that uses the Didactical Design Research (DDR) model. The population of the study consists of 32 students from the 11th grade of Nurul Huda Jannatun Vocational High School, while the sample is taken from 3 students using purposive sampling method. The research findings reveal the following student obstacles: lack of readiness to receive learning due to a lack of motivation in learning, lack of knowledge of formulas to solve problems, misinterpretation of problems leading to errors in calculations, lack of understanding of the concepts presented in the given problems, inability to answer questions involving two transformation concepts, inability to answer story problems, perception of teachers explaining the material too quickly and lacking easily understandable illustrations, and inadequate teaching materials that do not explain the material in detail for each part